Pemodelan Kinetika Pengeringan Daun Bidara (Ziziphus spina-christi (L.)) Dengan Metode Pengeringan Tenaga Surya - Nunik Lestari; Samsuar Samsuar (Jurnal Agritechno, 2022)
The drying method used can affect the drying characteristics and quality of the final product such as color parameters. The purpose of this research is to study the kinetics of Z. spina-christi leaves drying, find a mathematical model that best fits the drying characteristics, and analyze the color change of dried Z. spina-christi leaves and their brew. The drying process is carried out with 2 treatments, namely using a solar dryer and by drying in an open space using direct sunlight. There are 13 mathematical models of thin layer drying selected to simulate the drying characteristics of Z. spina-christi leaves. Identification of the Lab* value is used to calculate the browning index of the leaves due to the drying method used. The results stated that the solar power dryer could increase the drying rate of Z. spina-christi leaves, thus shortening the drying time. The Diffuision Approach model is the most accurate mathematical model in describing the drying characteristics of Z. spina-christi leaves for the two drying methods tested based on the resulting constant values. Each drying method affects the browning reaction of the dried Z. spina-christi leaves which also has an impact on the color of the brew, where drying in direct sunlight will produce a darker color of the dried leaves and brew.